Unfolded protein response in Gaucher disease: from human to Drosophila. - Maor, G.; Rencus-Lazar, S.; Filocamo, M.; Steller, H.; Segal, D.; Horowitz, M. (Orphanet journal of rare diseases, 2013)
In Gaucher disease (GD), resulting from mutations in the GBA gene, mutant ?-glucocerebrosidase (GCase) molecules are recognized as misfolded in the endoplasmic reticulum (ER). They are retrotranslocated to the cytoplasm, where they are ubiquitinated and undergo proteasomal degradation in a process known as the ER Associated Degradation (ERAD). We have shown in the past that the degree of ERAD of mutant GCase correlates with GD severity.Persistent presence of mutant, misfolded protein molecules in the ER leads to ER stress and evokes the unfolded protein response (UPR).We investigated the presence of UPR in several GD models, using molecular and behavioral assays.Our results show the existence of UPR in skin fibroblasts from GD patients and carriers of GD mutations. We could recapitulate UPR in two different Drosophila models for carriers of GD mutations: flies heterozygous for the endogenous mutant GBA orthologs and flies expressing the human N370S or L444P mutant GCase variants. We encountered early death in both fly models, indicating the deleterious effect of mutant GCase during development. The double heterozygous flies, and the transgenic flies, expressing mutant GCase in dopaminergic/serotonergic cells developed locomotion deficit.Our results strongly suggest that mutant GCase induces the UPR in GD patients as well as in carriers of GD mutations and leads to development of locomotion deficit in flies heterozygous for GD mutations.